Histopathological evoluation of multiparametric MRI targeted prostate biopsies - Özöver, İrem; Çakır, Aslı; Müezzinoğlu, Bahar; Uğur Erol, Cahide; Boz, Mustafa Yücel (Springer, 2018)
[Abstract Not Available]
WOS: 000443414102296
Keywords: MRI; Prostate; Multiparametric